Poverty, user fees and ability to pay for health care for children with suspected dengue in rural Cambodia - Manderson Lenore; Khun Sokrin (BMC, 2008)
Abstract User fees were introduced in public health facilities in Cambodia in 1997 in order to inject funds into the health system to enhance the quality of services. Because of inadequate health insurance, a social safety net scheme was introduced to ensure that all people were able to attend the health facilities. However, continuing high rates of hospitalization and mortality from dengue fever among infants and children reflect the difficulties that women continue to face in finding sufficient cash in cases of medical emergency, resulting in delays in diagnosis and treatment. In this article, drawing on in-depth interviews conducted with mothers of children infected with dengue in eastern Cambodia, we illustrate the profound economic consequences for households when a child is ill. The direct costs for health care and medical services, and added indirect costs, deterred poor women from presenting with sick children. Those who eventually sought care often had to finance health spending through out-of-pocket payments and loans, or sold property, goods or labour to meet the costs. Costs were often catastrophic, exacerbating the extreme poverty of those least able to afford it.